Ordinance No. 10: An Ordinance Prohibiting the Carrying of Concealed Deadly Weapons, and Fixing the Penalty Therefor, in The Lompoc Record, August 21, 1888, at 2 - (:unkn) unknown (My University, 1888)
Prohibited the concealed carry of any pistol, revolver, dirk, stiletto, or other dangerous or deadly weapon.
Keywords: CARRY - CONCEALED